Effect of polyethylene glycol on in vitro degradability of nitrogen and microbial protein synthesis from tannin-rich browse and herbaceous legumes - Getachew, G; Makkar, H P S; Becker, K (BRITISH JOURNAL OF NUTRITION, 2000)
Determination of microbial degradability of N is important in formulating a sound supplementation strategy for efficient utilisation of basal as well as supplementary diet components. In vitro degradability of N (IVDN) from tannin-containing browses (Acacia cyanophylla, Acacia albida, Acioa barteri and Quercus ilex) and two herbaceous legumes (Desmodium intortum andDesmodium uncinatum) was determined using the in vitro gas-production method coupled with NH3-N measurement in the presence and absence of a tannin-binding agent (polyethylene glycol (PEG), molecular mass 6000). Addition of PEG to tannin-containing feeds significantly (P < 0.05) increased in vitro gas and short-chain fatty acid (SCFA) production, and IVDN. The use of PEG as a tannin-binding agent increased IVDN from 28 to 59, 32 to 72, 19 to 40, 32 to 73, 40 to 80, and 26 to 77 % in A. cyanophylla, A. albida, A. barteri, D. intortum, D. uncinatum and Q. ilexrespectively. There was significant correlation between total phenolic compounds (total phenol, TP; total tannin, TT) in leguminous forages and percentage increase in IVDN on addition of PEG (P < 0.05; R-2 0.70 and 0.82 for TP and TT respectively). The difference in IVDN observed in the absence and presence of PEG indicates the amount of protein protected from degradation in the rumen by tannins. When measured after 24 h incubation, tannin-containing feeds incubated in absence of PEG resulted in higher microbial protein synthesis than in the presence of PEG. Addition of PEG significantly (P < 0.05) reduced the efficiency of microbial protein synthesis expressed as mu mol purine/mmol SCFA.
Keywords: microbial protein synthesis; Polyethylene glycol; protein degradability; Tannins

TANNIN LEVELS IN LEAVES OF SOME OAK SPECIES AT DIFFERENT STAGES OF MATURITY - Makkar, H P S; DAWRA, R K; Singh, B (JOURNAL OF THE SCIENCE OF FOOD AND AGRICULTURE, 1991)
Total phenolics, condensed tannins, degree of polymerisation, protein precipitation capacity, protein precipitable phenolics and specific activity (protein bound per unit tannins) were determined in the leaves of four oak species at different stages of maturation (4 days old to 1 year old). The content of total extractable phenols was higher in younger leaves in Quercus ilex Linn, Quercus semecarpifolia Sm and Quercus serrata Roxb, whereas in Quercus glauca Thunb the content was higher in the mature leaves. In all species studied, condensed tannins increased with maturation. Protein precipitation capacity had a trend similar to that of total phenols. In Q serrate and Q semecarpifolia the apparent degree of polymerisation increased, and the content of protein precipitable phenolics and specific activity decreased as the leaves matured. The decrease in protein precipitation capacity with maturation in these two species may be explained by both the decrease in the content and the change in the nature of phenols capable of binding proteins. Protein precipitation capacity was not detectable in Q ilex leaves. Protein precipitation capacity in the mature leaves decreased in the order of Q serrata > Q semecarpifolia > Q glauca > Q ilex.
Keywords: CONDENSED TANNINS; Tannins; TOTAL PHENOLS